Development of E-LKPD in Motion System Materials for High School Class Using PageFlip 3D Software - Afreni Hamidah; Diah Sefti Ayunasari; Erick Sanjaya (Postgraduate, University of Mataram, 2023)
The need for education in the 21st century is increasing. Technology facilities in learning are increasing rapidly and sophisticated. Technology must be utilized to the maximum with everyone, especially learners and teachers. E-LKPD is a worksheet or teaching material made using 3D PageFlip Software in accordance with technological developments. This research aims to develop, know the feasibility and know the response of teachers and learners to the electronic use of LKPD (e-LKPD) High School class XI motion system material using PageFlip 3D Software. This type of research is a Research and development or R&D with a development model referring to the ADDIE model. The developed product is validated by material experts and media experts, and then assessed by the teacher of class XI biology subjects. The data used is qualitative and quantitative data, obtained from the results of analysis of questionnaire calculations and interviews. The results from research and development that have been written in this paper, it can be concluded that the e-LKPD media developed can be used as an additional medium in the learning process in motion system materials